The Synergistic Effect of Nicotine and Staphylococcus aureus on Peri-Implant Infections - Hu, Yao; Zhou, Wen; Zhu, Chengguang; Zhou, Yujie; Guo, Qiang; Huang, Xiaoyu; Yang, Bina; Ren, Biao; Cheng, Lei (Frontiers in Bioengineering and Biotechnology, 2021)
Smoking is considered as a key risk factor for implant survival, however how it interacts with the pathogens in peri-implant infections is not clear. Here we identified that nicotine, the key component of cigarette smoking, can interact with Staphylococcus aureus and synergistically induce peri-implant infections in a rat osteolysis model. The nicotine-S. aureus combination group increased the gross bone pathology, osteolysis, periosteal reactions and bone resorption compared to the nicotine or S. aureus single treated group (P<0.05). Nicotine did not promote the proliferation of S. aureus both in vitro and in vivo, but it can significantly up-regulate the expression of spa, a key virulence factor of S. aureus. The nicotine-S. aureus combination also synergistically activated the expression of RANKL (receptor activator of nuclear factor kappa B ligand, P<0.05) to promote the development of peri-implantitis. The synergistic effects between nicotine and S. aureus infection can be a new target to reduce the peri-implant infections.